Identification of bronchoaspiration due to oropharyngeal dysphagia in patients with community pneumonia - Carvalho, Yonatta Salarini Vieira; Xerez, Denise Rodrigues; Araújo, Abelardo Queirós Campos de (Acta Fisiátrica, 2006)
Pneumonia is a pulmonary parenchyma inflammation that results from an infectious or inflammatory process, responsible for 5% of all deaths reported in the world; it usually affects individuals whose defense mechanisms are compromised. The close association between swallowing abnormalities and the predisposition to repetitive bacterial pneumonia and its association with neuromuscular disorders have been the aim of many studies. Aim: To propose a clinical protocol to detect bronchoaspiration in patients with pneumonia, without videofluoroscopy. Method: 70 patients with mean age of 67.5±16.3 years were submitted to two swallowing evaluation protocols, previously validated in literature: Tohara (2003) and Xerez (2002). Results: 62.9% (44/70) of the patients were considered aspirators by the clinical examination, which showed a significant statistical correlation with the presence of neurological disorders and reduction in the state of alertness (p <0.001). Conclusion: The clinical examination was able to detect the patients at risk for aspiration pneumonia. The association of risk factors should lead the healthcare team to exercise more caution when planning the diet of the patient with pneumonia, as it can be the aspiration type.